Rice farming and farmer income: a case study at Kota Utara Sub District, Gorontalo Province - Yanti Saleh; Amir Halid; Rifni Mobi (Program Magister Ilmu Ekonomi Pascasarjana Universitas Jambi, 2017)
This research purpose to analyze the effect of the input use in rice farming on the income of farmers and analyze the efficiency of input in the production of rice farming to know farmers income at Kota Utara Subdistrict. The data obtained and analyzed used Cobb-Douglas analysis production function and efficiency analysis using input (allocative efficiency). The results showed that the use of production inputs together affect to the rice farming of farmers income. The results of efficiency indicate that the use of each input such as land, labor, seeds, fertilizers Phonska, urea, spontaneous drugs, score score are inefficient in the use of production input. Therefore, it is necessary to be reduced to achieve efficient use of production inputs. Keywords: Rice Farming, Production Input, Production Efficiency